Diseño de una red de acceso FTTH con tecnología XGS-PON para el ISP SKYLINK SYSTEM del cantón Chambo de la provincia de Chimborazo - Pinduisaca Quishpe, Juan Carlos (2023)
The purpose of the project is to design an FTTH network with XGS-PON for the ISP SKYLINK SYSTEM, located in Chambo. The characteristics of XGS-PON are explored through bibliographic research. And based on field research, gather information on the current reality of the area, regarding the services provided by ISPs. Then, to design and simulate the FTTH network with QGIS and OPTISYSTEM software, and based on experimental and cross-sectional research, to collect the research data and test the hypothesis. The surveys provided a clear picture of internet access in the locality, cesting the latent needs of the selected sample. Three critical parameters such as Q-Factor, BER and attenuation were evaluated, evidenced that the use of XGS-PON based systems can be implemented by the ISP. The cost evaluation has shown that the acquisition of equipment with XGS-PON technology is a lucrative and viable investment for the ISP. It is recommended to implement a training program for users, as well as to establish periodic monitoring and maintenance of the network to ensure optimal performance. It is also suggested that consideration be given to adding optical amplifiers in the most distant areas to provide better support to distant customers.